Review of some actual methods of storage, processing and analysis of data from camera traps in zoological research - Ogurtsov, Sergey S.; Volkov, Vladislav P.; Zheltukhin, Anatoliy S. (Nature Conservation Research: Заповедная наука, 2017)
An overview of the main problems in collection, storage, processing and analysis of data obtained by camera traps is conducted. Basing on reviewed national papers related to this theme, the conclusion is drawn that there is need for a detailed description of methodological approaches and tools for data processing in national studies. The most common software among foreign researchers for camera trap data processing in biodiversity studies and conservation projects is presented. An overview of thematic software such as Photospread, Aardwolf, CameraTrapManager, MapView, CameraBase and DeskTEAM is provided. Advantages and disadvantages, as well as working methods are detailed in the study. The principles of image metadata storage, methods of extraction and processing are considered. Comparative analysis of the different software and approaches to use camera traps as a method of zoological research are provided. General recommendations regarding their use in protected areas are provided, illustrated by studies conducted in the Central Forest Reserve. The key characteristics of software for camera traps that should be considered when choosing a specific solution are identified. Primary characteristics are the ability to import all image metadata, quick and easy tagging, export to the majority of formats. Wishes to improve and discuss methodological approaches among national researchers are expressed. Despite a large variety of available technical means, the need to develop national software for working with camera trap data is separately noted. All listed software items are provided with download hyperlinks, and user's manual hyperlinks.